Peningkatan Kemampuan Mengajar Guru Melalui Teknik Supervisi Kelas - Bambang Herry Iriantoro (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2016)
Abstract: Improvement of Teaching Ability through The Class Supervision Technique. This study aims to improve the teaching skills of primary school teachers in learning through the implementation of supervision. The study was conducted in Gugus 3 Loceret the District Nganjuk with the design school action research, conducted in two cycles. The survey results revealed that the ability of teachers to teach elementary school could be improved through classroom supervision techniques. Improving the ability of teachers to teach is demonstrated by (a) increasing the ability to manage a class, (b) increasing the ability to use learning strategies, (c) increase the capacity to manage the interaction of classes, (d) an increase in the ability to help develop positive attitudes of students and (e) an increase in the ability to execute evaluation process and learning outcomes.Abstrak: Peningkatan Kemampuan Mengajar Guru melalui Teknik Supervisi Kelas. Penelitian ini bertujuan untuk meningkatkan kemampuan mengajar guru SD dalam pembelajaran melalui pelaksanaan supervisi. Penelitian dilakukan Gugus 3 Kecamatan Loceret Kabupaten Nganjuk dengan rancangan penelitian tindakan sekolah, dilaksanakan dalam 2 siklus. Hasil penelitian diketahui bahwa kemampuan mengajar guru SD dapat ditingkatkan melalui teknik supervisi kelas. Peningkatan kemampuan mengajar guru tersebut ditunjukkan oleh (a) peningkatan kemampuan mengelola kelas, (b) peningkatan kemampuan menggunakan strategi pembelajaran, (c) peningkatan kemampuan mengelola interaksi kelas, (d) peningkatan kemampuan membantu mengembangkan sikap positif siswa dan (e) peningkatan kemampuan melaksanakan evaluasi proses dan hasil belajar.